Inactivation of salmonella typhimurium E1366 in organic acid tumble soaked ox tripe - Valera, Ma. Celeste Barbosa; Gabriel, Alonzo, Alulod (2007)
ABSTRACT Citric, lactic, and tartaric acids were used against Salmonella Typhimurium E1366 in ox tripe to determine their effectiveness as antimicrobial agents using tumble soaking method. Three concentrations (2.5, 5.0, and 7.5) with varying tumbling times (5.0, 10.0, 7.5 minutes)were utilized in the experiment. The most effective acid was determined based on microbial, physicochemical, and sensory attributes of the treated tripes. Results showed that there was a significant relationship in varying concentration and the tumbling time of the organic acid treated sample. Based on overall parameters used, conclusion was reached that the best among the three organic acid was citric acid.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat -- Preservation; Meat -- Microbiology